2021
DOI: 10.1128/spectrum.00593-21
|View full text |Cite
|
Sign up to set email alerts
|

Novel Freshwater Cyanophages Provide New Insights into Evolutionary Relationships between Freshwater and Marine Cyanophages

Abstract: This study expands the current knowledge on freshwater cyanophage isolates and cyanophage genetic diversity, indicating that freshwater and marine cyanophages infecting Synechococcus spp. may share close genetic similarity and evolutionary relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Furthermore, the Pelagibacter siphovirus Kolga [ 100 ] and more than 20 autographiviruses showed significant sequence identity over a DNA primase, ribonucleotide diphosphate reductase subunits, and a few small hypothetical proteins ( Figure S13 ). Moreover, two Synechococcus siphoviruses, KBS-S-2A [ 101 ] and S-CBS4 [ 102 ], were similar to Synechococcus autographiviruses S-SRP02 [ 103 ], S-B28 (NC_048171.1), and S-SRP01 [ 104 ] through a few hypothetical proteins ( Figure S14 ). It has not escaped our attention that the above-mentioned phages of the SG3 subgraph infect similar hosts, that is, marine bacteria of the Alphaproteobacteria class (often of the same taxonomic genus).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the Pelagibacter siphovirus Kolga [ 100 ] and more than 20 autographiviruses showed significant sequence identity over a DNA primase, ribonucleotide diphosphate reductase subunits, and a few small hypothetical proteins ( Figure S13 ). Moreover, two Synechococcus siphoviruses, KBS-S-2A [ 101 ] and S-CBS4 [ 102 ], were similar to Synechococcus autographiviruses S-SRP02 [ 103 ], S-B28 (NC_048171.1), and S-SRP01 [ 104 ] through a few hypothetical proteins ( Figure S14 ). It has not escaped our attention that the above-mentioned phages of the SG3 subgraph infect similar hosts, that is, marine bacteria of the Alphaproteobacteria class (often of the same taxonomic genus).…”
Section: Resultsmentioning
confidence: 99%
“…Cyanophage research has concentrated on saline and freshwater aquatic environments [131]. A notable study has indicated genetic similarities between cyanophages in marine and freshwater systems [135]. Cyanophages such as Ma-LMM01, Ma-LBP, and VLP are known to specifically attack cyanobacteria that produce the toxin microcystin [136].…”
Section: Viruses For Habs Controlmentioning
confidence: 99%
“…The cyanophages, which specifically infect cyanobacteria, also possess very narrow host ranges. They are involved in regulating the abundance and population density of cyanobacteria, thus playing a key role in cyanobacterial community succession 8 . A-1(L) is a Myoviridae cyanophage isolated in 1970s 9 that specifically infects the model cyanobacterium Anabaena sp.…”
Section: Introductionmentioning
confidence: 99%